Integrated Investment Appraisal of a 400 Bed Hospital Project in the Kurdistan Region of Iraq Using FAST Modeling Standards - Bayiz, Lafaw Dara (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
The provision of healthcare services is one of the top priorities of the Kurdistan Regional Government (KRG). People living in this region have insufficient access to advanced healthcare services. Nevertheless, the limited healthcare services with regard to population growth in the region have grown 2.4% per year creating a serious deficiency in accessing modern healthcare services. In undertaking this investigation, the aim was to improve economic and social development in the region by providing a financial, economic and risk analysis of a 400 bed hospital project development in the KRG, with the expectation of alleviating healthcare service demands on existing facilities for many years ahead which will be another step to increase the quality of healthcare provided in this area. This study is based on cost-effectiveness analyses of the integrated investment appraisal technique. The strategy employed in this study is to move towards a more effective and better projection by carrying out the modeling of expected future healthcare service demands, a qualitative evaluation of various conversations with government officials, healthcare service providers and private sector healthcare service officers. This work focuses on a variety of internal and global policy areas such as financing, the fees charged by different earners and quality-adjusted life years. The study was conducted from May 2017 through May 2018. The necessary data for this investigation was obtained from the Ministry of Health Kurdistan-Iraq, KRG Statistics Office and Galala Construction Contracting Holding Ltd. The conclusions should be of concern to those interested in hospital project development in the Kurdistan Region of Iraq and specifically the Kurdistan Regional Government in guiding the Ministries of Planning and Health to develop targeted solutions to these critical issues faced by the KRG.

ÖZ: Sağlık hizmetlerinin sağlanması, Kürdistan Bölgesel Yönetimi'nin en önemli önceliklerinden biridir. Bu bölgede yaşayan insanlara iyi bir sağlık hizmeti sunulamamaktadır. Bununla birlikte, yılda ortalama %2.4 oranında nüfus artışına ilişkin sınırlı yapıda sağlık hizmetlerinin sunulması gelişmiş sağlık hizmetlerine sunulmasında yetersizlik yaratmıştır. Bu Araştırmayı yürütürken, bölgedeki sağlık hizmetlerini hafifletme beklentisi ile 400 yataklı hastane projesinin yapılması için finansal, ekonomik ve risk analizi yaparak bölgedeki ekonomik ve sosyal gelişmeyi iyileştirmeyi amaçlamıştır. Bu proje, mevcut hastanelerin üstündeki sağlık hizmeti taleplerini azaltması açısından bir başka adım olacaktır. Bu çalışma, entegre yatırım değerlendirme tekniğinin maliyet etkililik analizlerine dayanmaktadır, çalışmada kullanılan strateji ve gelecekteki sağlık hizmetleri taleplerinin modellenmesi gibi faktörler hükümet ve özel sektör sağlık hizmeti görevlileriyle yapılan çeşitli görüşmelerin nitel bir değerlendirmesi yapılarak ele alınmıştır. Bu araştırmada hastaların ekonomik gelirleri göz önünde bulundurularak ödenen ücretler farklı bir şekilde hesaplanmıştır. Bunun yanısıra, proje finanse etmek ve kaliteli yaşam yılları gibi çeşitli faktörlere odaklanmaktadır. Bu çalışma, Mayis 2017'den Mayis 2018'e tarihleri arasında gerçekleştirilmiştir ve gerekli veriler Kürdistan bölgesel yönetimi sağlık bakanlığı, İstatistik Ofisi ve Galala İnşaat Taahhüt Holding Ltd.'den elde edinmiştir. Bu çalışmadaki sonuçlar, Kürdistan Bölgesinde hastane projesinin uygulunmasında yol gösterici bir çalışmadır. Ayrıca , Planlama Bakanlığına ve Sağlık Bakanlığı'nın karşılaştığı problemlere yönelik çözümler geliştirmek için hazırlanmıştır.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2018. Supervisor: Assoc. Prof. Dr. Hasan Ulaş Altıok.
Keywords: Banking and Finance; Hospital Project--Financial Analysis and Management--Kurdistan Region (Irag); Cost-effectiveness Analysis; Healthcare Services; Hospital Project; Economic Analysis; Financial Analysis; Risk Analysis; Kurdistan Region of Iraq